Motivasi Dan Tantangan Adopsi Mobile Payment: Perubahan Perilaku Konsumen Dan Transformasi Industri Keuangan - Handayani, Made Mulia; Rahmantari, Ni Luh Laksmi (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The development of digital technology has transformed transaction methods with innovations in mobile payment. This study aims to explore the motivations behind mobile payment adoption, focusing on psychological aspects, internal and external motivations, as well as the challenges encountered. Previous research highlights convenience and efficiency as key factors in the adoption decision, while challenges such as security and digital identity risks must be addressed. A qualitative method was used, employing semi-structured interviews with 20 participants from Ngurah Rai University and Tabanan University, based on the Theory of Planned Behavior. The findings reveal that internal motivations, such as ease of use and practical benefits, as well as external factors, including social influence, affect adoption. The main obstacles include technical issues and initial adaptation challenges.